Two Samaritan Interpretations of Genesis 6: 3 - شحادة, حسيب (lark, 2019)
Abstract:“And Shehmaa said, My Spirit shall not strive with man forever, whether he is bone or flesh, And his days shall be one hundred and twenty years’’, is recited today by the Samaritans as: wyǡ˒ūmƏr šēmå lǡ yēdon ruwwi bǡdåm lūlåm afšågåm ū bǡšår wǡyyu yǡmo mǡ: wišrƏm šēna. Various interpretations of this verse have been suggested, particularly regarding the expression “lǡ yēdon ruwwi”. Different renderings have also been given the verse in Samaritan Aramaic (Targum) and in Samaritan Arabic translations of the Torah, as well as in modern Christian Arabic translations. Each of the Samaritan Aramaic translation (Targum) of the Torah, as well as the Arabic translation has an old version and a newer version. In Aramaic both versions are anonymous, but in Arabic the old version is ascribed to the prominent Samaritan scholar, Isḥāq (Abū Ibrahīm) b. Marḥīv (Farağ) b. Mārūṯ, known as Abū al-Ḥasan al-Ṣūrī (Av Ḥisda the Tyrian), between the end of the eleventh century and the beginning of the twelfth century in Damascus.
Keywords: Two Samaritan interpretations of Genesis 6: 3; Ṣadaqah the physician; 13th cent; 19th cent.; Pinḥas b. Ṭavia; manuscripts